Comparative Effectiveness of Transurethral Resection Techniques in the Inpatient Setting for Benign Prostatic Hyperplasia. Issue 5 (September 2018) - Meyer, Christian P.; Friedlander, David F.; Wang, Ye; Hollis, Michael; Lipsitz, Stuart R.; Eswara, Jairam; Kathrins, Martin; Bhojani, Naeem; Chughtai, Bilal; Sun, Maxine; Chung, Benjamin I.; Chang, Steven L.; et al.
Abstract : Introduction: : Monopolar transurethral resection is the conventional surgical standard of care for bladder outlet obstruction due to benign prostatic enlargement. Bipolar resection and GreenLight™ photovaporization have emerged as options with favorable safety profiles. The literature comparing these modalities is limited by sample size and absence of cost data. We compared costs and short‐term safety of monopolar, bipolar and laser vaporization techniques in an all‐payer inpatient discharge database. Methods: : A total of 20, 323 men 40 to 80 years old with a diagnosis of benign prostatic hyperplasia who underwent an outlet procedure between 2003 and 2013 were identified in the Premier Research Database. Using propensity weighted logistic regression we assessed treatment trends and perioperative safety outcomes. Results: : Monopolar resection remained the most commonly performed procedure between 2003 and 2013. However, its use decreased by 20% (p <0.001). Whereas there were no differences between bipolar and monopolar resection with regard to operative time (p >0.99), length of stay (p=0.82) and 90‐day complication rates (p=0.34), GreenLight photovaporization was associated with prolonged operative time (+12 minutes, 95% CI 10.25 to 13.75, p <0.001) and shorter length of stay (OR 0.51, 95% CI 0.37 to 0.7, p <0.001) compared to monopolar resection. Bipolar resection (982, 95% CI 509–1, 456; p <0.001) and GreenLight photovaporization (1, 536; 95% CI 1, 296–1, 775; p <0.001) were associated with greater 90‐day direct hospital costs than monopolar resection. GreenLight photovaporization was associated with decreased odds of dilutional hyponatremia, stricture formation and prostatitis relative to monopolar resection. Conclusions: : We found a modest perioperative safety benefit with bipolar resection and GreenLight photovaporization relative to monopolar resection. However, both procedures were associated with higher costs.